2018
DOI: 10.1186/s12932-018-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the phosphorus forms extracted from soil by the Mehlich III soil test

Abstract: Phosphorus (P) can limit crop production in many soils, and soil testing is used to guide fertilizer recommendations. The Mehlich III (M3) soil test is widely used in North America, followed by colorimetric analysis for P, or by inductively coupled plasma-based spectrometry (ICP) for P and cations. However, differences have been observed in M3 P concentrations measured by these methods. Using 31P nuclear magnetic resonance (P-NMR) and mass spectrometry (MS), we characterized P forms in M3 extracts. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Whilst this signal would be considered to have a relatively slow decay due to its narrow line-width, the peak is similar to that reported in large molecular weight fractions (> 10 kDa) by McLaren et al (2015a). Its presence has also been suggested in unfractionated soil extracts (Cade-Menun et al, 2018). Our results support its association with organic P in large molecular weight fractions and suggest that it should be considered in relation to the broad signal.…”
Section: Transverse Relaxation (Carr-purcell-meiboom-gill) Experimentssupporting
confidence: 85%
“…Whilst this signal would be considered to have a relatively slow decay due to its narrow line-width, the peak is similar to that reported in large molecular weight fractions (> 10 kDa) by McLaren et al (2015a). Its presence has also been suggested in unfractionated soil extracts (Cade-Menun et al, 2018). Our results support its association with organic P in large molecular weight fractions and suggest that it should be considered in relation to the broad signal.…”
Section: Transverse Relaxation (Carr-purcell-meiboom-gill) Experimentssupporting
confidence: 85%
“…However, the ICP measures all forms of P, including the colorless organic phytate compound, which explains the higher M3‐P ICP values for alum‐treated litter. The presence of phytate and other inositol hexakisphosphate compounds in soil M3‐P extracts was recently confirmed by Cade‐Menun et al (2018).…”
Section: Resultsmentioning
confidence: 74%
“…However, the ICP measures all forms of P, including the colorless organic phytate compound, which explains the higher M3-P ICP values for alum-treated litter. The presence of phytate and other inositol hexakisphosphate compounds in soil M3-P extracts was recently confirmed by Cade-Menun et al (2018). Another explanation for the differences observed in P concentrations between colorimetry and ICP is the presence of colloidal-sized Al-P minerals in soil.…”
Section: Vertical Distribution Of Soil Phosphorusmentioning
confidence: 75%
“…This implies that soil extraction condition significantly affected the recovery of nitrogen. Moreover, [ 33 ] in their study has reported TNP recovery are 39% to 97%. DOC studied by [ 34 ] implies a higher recovery accounted for almost 58.8–84.5% of the total DOC.…”
Section: Discussionmentioning
confidence: 94%